Pipeline Embolization Device for Treatment of Extracranial Internal Carotid Artery Pseudoaneurysms: A Multicenter Evaluation of Safety and Efficacy. Issue 4 (24th January 2020) - Akinduro, Oluwaseun O; Gopal, Neethu; Hasan, Tasneem F; Nourollah-Zadeh, Emad; Vakharia, Kunal; De Leacy, Reade; Burkhardt, Jan-Karl; Yamamoto, Junichi; Mocco, J; Castilla, Leonardo Rangel; Tze Man Kan, Peter; Boulos, Alan; et al.
Abstract: BACKGROUND: There is a paucity of literature regarding treatment options for extracranial pseudoaneurysms of the internal carotid artery (ICA). To date, Pipeline Embolization Device (PED; Medtronic Inc) use for the treatment of extracranial pseudoaneurysms of the ICA has only been reported from single-center case series. OBJECTIVE: To evaluate the safety and efficacy of PED for the treatment of extracranial ICA pseudoaneurysms. METHODS: This is a multicenter retrospective study involving 6 high-volume tertiary academic institutions in the United States. We analyzed patients with extracranial ICA pseudoaneurysms treated with PED between January 1, 2011, and January 1, 2019. Clinical assessment was performed pre- and postintervention using the modified Rankin Scale (mRS) and National Institution of Health Stroke Scale (NIHSS) at a minimum of 4-mo follow-up. RESULTS: A total of 28 pseudoaneurysms with a mean diameter of 17.7 mm (range: 4.1-52.5 mm) were treated with PED in 24 patients at 6 participating centers. The mean age was 52.1 yr (17-73) ± 14.3 with 14 females and 10 males. At a mean of 21-mo (range 4-66 mo) follow-up, complete occlusion was achieved in 89% (n = 25/28), with near-complete occlusion (>90% occlusion) in the remainder. There were no periprocedural complications. Postprocedure NIHSS was 0 in 88% (n = 21/24) and 1 in 12% (n = 3/24) of patients, and mRS was 0 in 83% (n = 20/24) and 1 in 17% (n = 4/24) of patients. CONCLUSION: The treatment of extracranial ICA pseudoaneurysms with PED is safe and effective in selected patients. Randomized controlled trials and prospective cohort studies are needed to establish the role of flow diversion for ICA pseudoaneurysms. Graphical Abstract: